Permanent nursing education in family health strategy - Rossandra Ribeiro Marreiros de Araújo; Maria Eliete Batista Moura; Benevina Maria Vilar Teixeira Nunes; Eliana Campelo Lago; Inez Sampaio Nery (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: to analyze the permanent education process of Nurses in the Family Health Strategy and its relationship with the quality of the care provided. Methodology: This is a qualitative research, carried out with 26 Nurses of Primary Healthcare Units. The data were collected from April to June 2012, by means of semi-structured interview, processed in Alcest 4.8 and analyzed by descending hierarchical classification. Results: They were presented in four classes, namely: the availability of nurses for trainings; the permanent education policy; the quality of nursing work and vocational training through the introductory course and specialization. Conclusion: The permanent education process of nurses in the Family Health Strategy depends on the Permanent Education Policy adopted in the municipality, with the training of nurses. The permanent education is directly related to the quality of care.